KERUKUNAN ANTARUMAT BERAGAMA DALAM PERSPEKTIF HUKUM PIDANA - Esther, July (Universitas Borneo Tarakan, 2016)
Abstract Religious diversity is often a challenge in harmony, there is still statically addressed (exclusive), has not led to a motion proactive in building unity among religious. Harmony among religious believers in the perspective of criminal law refers to one of the articles in the Code of Penal about setting Crimes Against Public Order, namely Article 156a, which is the rider with the Presidential Decree of the Republic of Indonesia Number 1 / the 1965 on the Prevention of Abuse and / or blasphemy. Treatment of the perpetrators either individual or organization or belief is preceded procedural measures and stages of criminal sanctions for perpetrators of violations of Article 1 of the Republic of Indonesia Presidential Decree No. 1 / the 1965 as the final sanction which wants peace.Keywords: harmony, religious communities, the criminal law.